THE EFFECT OF INJECTION SPEED, INJECTION PRESSURE, AND MOLD POSITION ON THE PRODUCTION OF POLYPROPYLENE (PP) LOUNGE CHAIRS - Wisnu Pambudi; Muhamad Choirul Mahfudin (Politek ATK Yogyakarta Press, 2022)
Injection molding is making products made from plastic materials through melted plastic and then injected into a mold or mold. The plastic lounge chair is made of polypropylene (PP) by injection molding. In the injection molding process, there are parameters of injection speed, pressure, and molding position. This study aims to determine the effect of injection speed, pressure, and mold position. Injection speed, injection pressure, and improper mold position can produce a lounge chair with short-shot defects. Short-shot defects cannot be repaired but must be recycled by chopping them up to be reused as additional material for producing plastic products; this will increase operational costs. Efforts to reduce short shots can be done by changing the speed parameter settings, injection pressure, and mold position. Plastic lounge chairs, according to standards, were obtained by inverted mold position and injection speed settings in zones 1, 2, 3, 4, and 5 of 70, 60, 50, 45, and 30 in mm/s units. The injection pressures are 95, 85, 75, 65, and 55 bar.